2021
DOI: 10.5751/es-12717-260414
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends and perceptions of sea turtle egg consumption in Redang Island, Malaysia

Abstract: Sea turtles have been exploited at unsustainable rates globally. In Malaysia, their populations have faced serious declines because of diverse anthropogenic stressors including turtle egg consumption. Redang Island, off the northeast coast of Peninsular Malaysia, is an important rookery for green sea turtles (Chelonia mydas) in Southeast Asia. The local community has depended on turtle eggs as a food and livelihood source for decades. Owing to the precipitous decline in sea turtles, the main nesting beaches be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…For instance, household size was found to have a negative correlation to fish consumption [ 109 ]. Further, socio-demographic characteristics—age [ 64 , 110 , 114 , 115 , 116 , 117 ], gender [ 64 , 110 , 116 , 118 ], education [ 110 , 114 , 116 , 118 , 119 , 120 ], marital status [ 114 , 115 ], occupation [ 119 ], number of household members [ 109 , 115 , 118 ], income [ 108 , 109 , 110 , 115 , 116 , 119 , 121 , 122 ], ethnicity [ 114 ], religion [ 116 , 123 ], and place of residence [ 108 , 114 , 115 , 117 ]—were significantly associated with aquatic food consumption. Overall, older male consumers with higher income and education residing either in an urban setting or coastal region tend to have higher aquatic food consumption levels in Asia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, household size was found to have a negative correlation to fish consumption [ 109 ]. Further, socio-demographic characteristics—age [ 64 , 110 , 114 , 115 , 116 , 117 ], gender [ 64 , 110 , 116 , 118 ], education [ 110 , 114 , 116 , 118 , 119 , 120 ], marital status [ 114 , 115 ], occupation [ 119 ], number of household members [ 109 , 115 , 118 ], income [ 108 , 109 , 110 , 115 , 116 , 119 , 121 , 122 ], ethnicity [ 114 ], religion [ 116 , 123 ], and place of residence [ 108 , 114 , 115 , 117 ]—were significantly associated with aquatic food consumption. Overall, older male consumers with higher income and education residing either in an urban setting or coastal region tend to have higher aquatic food consumption levels in Asia.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, older male consumers with higher income and education residing either in an urban setting or coastal region tend to have higher aquatic food consumption levels in Asia. In contrast, other studies have indicated that age [ 108 , 118 , 120 ], gender [ 114 , 119 ], income [ 117 ], marital status [ 108 ], number of household members [ 108 ], and religion [ 113 ] had no significant association with aquatic food consumption.…”
Section: Resultsmentioning
confidence: 99%
“…Sea turtle conservation programs in Malaysia have been implemented many years ago in many ways particularly, policy and legislation development (Abd Mutalib et al 2013;Abd Mutalib and Fadzly 2015;WWF-Malaysia 2010, 2012Mohd Jani et al 2020;Poti et al 2021); turtle egg protection and hatchery programs (Chan 2013;Abd Mutalib and Fadzly 2015;Mohd Jani et al 2020); educational and awareness programs (WWF-Malaysia 2010, 2012Chan 2013;Abdullah and Halim 2018) as well as institutional management programs (Chan 2013;Mohd Jani et al 2020). Despite the widespread decline of turtle population in Terengganu and their ecological importance, one way to support turtle conservation programs is to demonstrate the economic importance of marine turtles by demonstrating an economic valuation.…”
Section: Methodsmentioning
confidence: 99%
“…Increased regulation of harvests generally was implemented after a dramatic decline in leatherback turtle nests at Rantau Abang in Terengganu -from some 10,000 nests per year in 1956 to just three in 2002 (Troëng and Drews, 2004), attributed to both continuous exploitation of eggs over decades, and fisheries bycatch of adults (Chan and Liew, 1996;Eckert et al, 2012;NMFS and USFWS, 2020). However, at least on Redang Island, Terengganu, legal protection of turtle nesting beaches as well as changing attitudes toward egg consumption, are thought to have led to a decline in demand for green turtle eggs, although consumption continues (Poti et al, 2021). Population declines of leatherback turtles in Terengganu contrast with recoveries of green turtles in Sabah, following the strong enforcement of the egg protection programme in the early 1970s (Chan, 2006).…”
Section: Cheloniansmentioning
confidence: 99%